Application Of The Inquiry Learning Model In Improving Student Learning Outcomes In Biology Science Learning At SMP Negeri 6 Tondano - Sri Dewinta Kurais; Meity N. Tanor; Carolin Manuahe (Institut Nalanda, 2023)
Inquiry-based learning refers to a sequence of educational activities that aim to fully engage students in methodical, critical, logical, and analytical processes of searching and investigating. The ultimate goal is for students to independently develop their own discoveries with a high level of confidence. This study aims to find out the students' mastery learning results by using the inquiry learning model in which the material is related to the structure and function of plant parts. This research is classroom action research. This research was conducted at SMP Negeri 6 Tondano. The research subjects were class VIII students, totaling 27 people. The results showed that the percentage of learning completeness in cycle I was 29.63% with an average score of 60.62, and cycle II was 92.60% with an average score of 81.07. The results of this study indicate that learning the structure and function of plant parts using the inquiry learning model can improve student learning outcomes.